2022
DOI: 10.1155/2022/9225647
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl Dextran‐Based Nanomicelle Coatings on Microarc Oxidized Titanium Surface for Percutaneous Implants: Drug Release, Antibacterial Properties, and Biocompatibility

Abstract: Bacterial contamination and biofilm formation onpercutaneous implants can lead to device failure and be life-threatening. To solve this issue, we constructed a carboxymethyl dextran- (CMD-) based nanomicelle antibacterial coating on the microarc-oxidized titanium (MAO-Ti) surface (described in the supplementary file). The self-assembled CMD-based nanomicelles and octadecylamine (ODA) were developed as a drug carrier and loaded with minocycline (MC). The characterization and stability of the MC-loaded nanomicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Due to its good biocompatibility, biodegradability and anti-inflammatory effect, gelatin has been widely used in the food, cosmetic, tissue engineering and pharmaceutical industry [33]. Gelatin has also been widely used as a cross-linking agent to cross-link nanoparticles to the surface of MAO coating to fabricate composite coating [20,23]. SEM images showed that the pH-sensitive double-layered nanoparticles were well distributed and tightly cross-linked with each other and the wall of pores by gelatin (figure 1(F)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its good biocompatibility, biodegradability and anti-inflammatory effect, gelatin has been widely used in the food, cosmetic, tissue engineering and pharmaceutical industry [33]. Gelatin has also been widely used as a cross-linking agent to cross-link nanoparticles to the surface of MAO coating to fabricate composite coating [20,23]. SEM images showed that the pH-sensitive double-layered nanoparticles were well distributed and tightly cross-linked with each other and the wall of pores by gelatin (figure 1(F)).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this technique can form a porous structure and then produce various composite coatings. Minocycline-loaded nanomicelles were incorporated into the pores of MAO treated titanium (MAO-Ti), and the composite coating showed excellent antibacterial ability [20]. Zhou fabricated a composite dopamine-nanoclay coating on MAO-Ti by immersion method, which could significantly stimulate osteoblast adhesion, proliferation, and osteogenic differentiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…A new antibacterial coating was fabricated using carboxymethyl dextran (CMD) and microarcoxidized titanium (MAO-Ti) [ 56 ]. The coating was designed to release minocycline (MC) using self-assembled nanocells made of CMD and octadecylamine (ODA).…”
Section: Overview On Polysaccharide-based Drug Delivery Systemsmentioning
confidence: 99%
“…The coating reduced the number of S. aureus and improved the viability, adhesion, and morphology of the human skin fibroblasts compared to smooth titanium films/sheets. The MC-loaded CMD-based nanocells coated on a MAO-Ti surface (MC@(ODA-CMD)CL-Ti) have great potential as coatings for percutaneous implants due to their sustained-release properties, excellent antibacterial properties, and biocompatibility [ 56 ].…”
Section: Overview On Polysaccharide-based Drug Delivery Systemsmentioning
confidence: 99%